A Dual Band Non-Concentric Circular Rings Microstrip Antenna Design for Wi-Fi Application - Kareem Madhloom Gatea (مجلة النهرين للعلوم الهندسية)
In this paper we design a dual band patch antenna for Wi-Fi application and using it works in two different frequencies the first one in bandwidth of 480 MHz and impedance bandwidth of 18.75% (2.32. to 2.8 GHz) with resonant frequency 2.56 GHz this band can cover the Wi-Fi   the second bandwidth is 4 GHZ and the impedance bandwidth 53.33% (5 GHz – 9 GHz). With resonant frequency 7.5 GHz, this band of frequency can cover the WLAN 5.8GHz, the 6GHz band its operate at frequency range (5.925 - 7.125 GHZ) it used for unlicensed Wi-Fi with bandwidth of 1.2 GHZ its application on Wi-Fi 7 and Wi-Fi 6E. Another application of the antenna in 8 GHz band its operate at the range (7.725 – 8.275 GHz). We use the CST package to design and simulated the propose antenna with dimensions of 35 mm×21 mm×1.6 mm.